1997
DOI: 10.1073/pnas.94.15.7873
|View full text |Cite
|
Sign up to set email alerts
|

Human and Saccharomyces cerevisiae dolichol phosphate mannose synthases represent two classes of the enzyme, but both function in Schizosaccharomyces pombe

Abstract: Dolichol phosphate mannose (Dol-P-Man), formed upon transfer of Man from GDPMan to Dol-P, is a mannosyl donor in pathways leading to N-glycosylation, glycosyl phosphatidylinositol membrane anchoring, and Omannosylation of protein. Dol-P-Man synthase is an essential protein in Saccharomyces cerevisiae. We have cloned cDNAs encoding human and Schizosaccharomyces pombe proteins that resemble S. cerevisiae Dol-P-Man synthase. Disruption of the gene for the S. pombe Dol-P-Man synthase homolog, dpm1 ؉ , is lethal. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
94
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 38 publications
2
94
0
Order By: Relevance
“…The human and fission yeast enzymes lack a C-terminal hydrophobic domain, whereas the trypanosome and budding yeast enzymes contain one. The two classes of this enzyme, however, are functionally equivalent, because both the human and S. cerevisiae genes can complement a lethal null mutant in fission yeast (Colussi et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human and fission yeast enzymes lack a C-terminal hydrophobic domain, whereas the trypanosome and budding yeast enzymes contain one. The two classes of this enzyme, however, are functionally equivalent, because both the human and S. cerevisiae genes can complement a lethal null mutant in fission yeast (Colussi et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This type of variation between ER isoenzymes involved in GPI biosynthesis is not unprecedented. Two classes of dolicholphosphate-mannose synthase have been identified in differ- ent species (Colussi et al, 1997). The human and fission yeast enzymes lack a C-terminal hydrophobic domain, whereas the trypanosome and budding yeast enzymes contain one.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the MsPpm1-MsPpm2 interaction is reminiscent of that of the mammalian Dpm1 with Dpm3 (8,9). In contrast, MsPpm1 is functionally active when expressed in Escherichia coli, similarly to the S. cerevisiae group of Dol-P-Man synthases (7,17). As a consequence, MsPpm1 may constitute a new intermediate group of Polyprenol-P-Man synthases.…”
mentioning
confidence: 90%
“…Sequence analysis has suggested that the Dol-P-Man synthase can now be divided into two classes: one includes the enzymes from S. cerevisiae, U. maydis, Trypanosoma brucei, and Leishmania mexicana (29,30). They share 50 -60% amino acid identity and have a stretch of hydrophobic amino acid residues near the COOH terminus constituting a transmembrane domain.…”
mentioning
confidence: 99%
“…Dol-P-Man synthase has now been cloned from a number of species such as Trypanosoma brucei, Ustilago maydis, Schizosaccharomyces pombe, Caenorhabditis briggsiae as well as from humans by complementation of a temperature-sensitive S. cerevisiae DPM1 mutant, or by cDNA cloning (27)(28)(29). Sequence analysis has suggested that the Dol-P-Man synthase can now be divided into two classes: one includes the enzymes from S. cerevisiae, U. maydis, Trypanosoma brucei, and Leishmania mexicana (29,30).…”
mentioning
confidence: 99%